Brazil and Turkey in the early twentieth century: Intertwined and parallel stories of educational history - Warde, Mirian Jorge [UNESP] (Springer Nature, 2013)
Historiography is rich in examples of efforts to respond to issues concerning the emergence of similar cultural patterns, in cultures distant in either time or space. Many historians have employed the concept of network as alternative to the idea of influence, which implies, at least, unidirectional relations, steady in space and in time, between individuals, groups, and even entire societies; more than that, the idea of influence brought from the most ancient history of ideas is based on the (psychological) assumption that one pole ascends the other. The first pole is adult, developed, and civilized; and the other is infantile, underdeveloped, and primitive. Although there is evidence in favor of these new historiographical trends, historians of education have been shown to be averse to some conceptual and methodological revisions affecting that central idea and some of its prerequisites, such as national borders and linear temporality. The split between Eastern and Western culture/education is one of the most unequivocal products of that framework.